Kajian Sosioekonomi Eksistensi Umbul Senjaya Kabupaten Semarang - Putra, Idos Febriyana; Pratama, Yogi Pasca; Samudro, Bhimo Rizky (EP FEB UNS, 2014)
This research is motivated from the existence of Senjaya Springs where can survive even only supported by community with limited capabilities. Therefore this study aims to: (1) determine the patterns of how myth affect the sustainability of Senjaya Springs until today. (2) Determine any motive and motivation behind the individual to perform the ritual. (3) Based on the motives anf motivation of preparators, whether the practice of Tapa Kungkum can be said to be rational when viewed from an economic standpoint.The focus of the analysis in this study is, what affects the existence of te springs and what the socioeconomic impacts for the community. Thus the informant targeted are : (1) person who knows the ins and out of Senjaya Spring. (2) Person directly affected by existence of Senjaya Springs. This study used a qualitative method using a phenomenological approach and historical narrative. The data in this Senjaya Springs study were collated by using several methods, namely : (1) in-depth interviews and unstructured interviews; and (2) participant observation.The results showed that: (1) there are 3 patterns of myth in maintaining the existence of Senjaya Springs. (2) There are 4 motives and motivations from two types of visitor in Senjaya Springs. (3) Tapa Kungkum regarded as a rational choice. The recommendations idea given to the village officer: (1) need serious management and development for tourist destination. (2) The need for adding infrastructure to facilitate for ritual actors at night.Keywords : Senjaya Springs, Myth, Socio-economic, Rational Choice TheoryJEL Classification : Z13